(untitled) (Tempo e Argumento, 2021)
Theobjective of this paper is to analyze the construction of a past drawn by two female historians from São Paulo University, Maria Odila Leite da Silva Dias and Maria de Lourdes Monaco Janotti. In the early 1970’s, both scholars wrote their doctoral thesis in which they took a past from the 19th century to temporalize the brazilian historiography, so that such works are taken as sources of investigation in this paper. How this past temporalization happened? Starting from this question and analyzing together those two productions, a nationalization and disciplinarization of the past of Brazilian historiography is discussed, highlighting some gender issues related not only to these points, but also about to the professional trajectory of historians. Keywords: Brazilian historiography; 1970’s; disciplinary past